Pengaruh Penggunaan Media Game Berbasis Wordwall terhadap Minat Dan Hasil Belajar Peserta Didik Kelas VII MTs Negeri 6 Bulukumba - A. Masrurah Aswidyaningrat; Sitti Rahma Yunus; Rifda Nur Hikmahwati Arif (Celebes Science Education, 2024)
This study aims to determine: 1) How high is the level of interest in learning of VII grade students of MTs Negeri 6 Bulukumba who use wordwall-based game media and conventional media, 2) How high is the level of learning outcomes of class VII MTs Negeri 6 Bulukumba who use wordwall-based game media and conventional media, 3) How high is the increase in science learning outcomes of class VII MTs Negeri 6 Bulukumba students who use Wordwall-based game media and conventional media, 4) Is there an effect of using Wordwall-based game media on interest and science learning outcomes in class VII students of MTs Negeri 6 Bulukumba. This type of research is quasi-experimental design research with a research design using Nonequivalent Control Group. The population of all VII grade students at MTs Negeri 6 Bulukumba in the 2022/2023 academic year consisted of 8 classes with a total of 278 people. The sample was selected by purposive sampling with 2 classes, namely the experimental class (VII.1) totaling 23 and the control class (VII.2) totaling 22 people. The research instrument was a questionnaire of learning interest and a learning outcomes test. The data were analyzed with descriptive statistics and inferential statistics. The results of the analysis showed that there was an effect of using wordwall-based game media on learning interest and science learning outcomes in class VII students of MTs Negeri 6 Bulukumba.